Performance assessment of the stacked microbial desalination cells with internally parallel and series flow configurations. Issue 4 (August 2018) - Ziaedini, Ali; Rashedi, Hamid; Alaie, Ebrahim; Zeinali, Majid
Abstract: Performances of five phenol-powered stacked microbial desalination cells (sMDC) with internally parallel and series continuous flow configurations were assessed. The effects of inter-membrane distance (5 and 10 mm) and flow configuration on water desalination were investigated in order to improve the flexibility and footprint of the system. Different sMDC configurations were examined with influent NaCl concentrations of 1–3% at flow rates of 3.5, 7, and 15 μL min −1 . The results of the series flow configurations showed that at NaCl concentration of 1%, reducing the inter-membrane distance (from 10 to 5 mm) of the desalination chamber next to the anode compartment resulted in improved desalination efficiency and specific desalination rate (SDR) while at 3% NaCl concentration, the highest desalination efficiency was achieved with 10 mm inter-membrane distance of both desalination chambers. The results of the parallel flow configurations showed that decreasing the inter-membrane distance leads to distinct effects on desalination efficiency based on the initial NaCl concentration. At NaCl concentration of 1% in contrast to the higher concentrations of 2–3%, an increase in desalination efficiency (36%) was achieved by decreasing the inter-membrane distance. Overall, in parallel flow configurations, the SDR trend was incremental (16–277%). It can be concluded that the different behavior of the sMDC at high and low NaCl concentrations should be taken into consideration in order to optimize the design and operation of these desalination systems.